2003
DOI: 10.1097/01.alc.0000057941.57330.39
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Alcoholics Anonymous: Intended and Unintended Change Mechanisms

Abstract: This article is a compilation of the information presented at a symposium at the 2001 RSA Meeting in Montreal, Canada. The presentations were: (1) Maintaining change after conjoint behavioral alcohol treatment for men: the role of involvement with Alcoholics Anonymous, by Barbara S. McCrady and Elizabeth E. Epstein; (2) Changing AA practices and outcomes: Project MATCH 3-year follow-up, by J. Scott Tonigan; (3) Life events and patterns of recovery of AA-exposed adults and adolescents, by Patricia L. Owen and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 33 publications
4
54
0
2
Order By: Relevance
“…There is a large body of literature documenting the links between beliefs regarding religion or spirituality, drinking self-effi cacy, and purpose in life with AA involvement (Carroll, 1993;Connors et al, 2001;Morgenstern et al, 1997;Owen et al, 2003;Project MATCH Research Group, 1997;Timko et al, 2006;Tonigan et al, 2002). Thus, we expected higher participation in faith-based practices, confi dence in one's ability to resist drinking, and purpose in life to predict initial AAH.…”
Section: Predictors Of Aa Involvementmentioning
confidence: 95%
“…There is a large body of literature documenting the links between beliefs regarding religion or spirituality, drinking self-effi cacy, and purpose in life with AA involvement (Carroll, 1993;Connors et al, 2001;Morgenstern et al, 1997;Owen et al, 2003;Project MATCH Research Group, 1997;Timko et al, 2006;Tonigan et al, 2002). Thus, we expected higher participation in faith-based practices, confi dence in one's ability to resist drinking, and purpose in life to predict initial AAH.…”
Section: Predictors Of Aa Involvementmentioning
confidence: 95%
“…The results of Project MATCH suggested that TSF was comparable with cognitive-behavioral therapy and motivational enhancement therapy on most outcomes of several indicators of measures of abstinence and superior to the others at the 3-year follow-up (Project MATCH Research Group, 1998). TSF has also been associated with higher rates of self-help involvement, which in turn has been associated with less alcohol use (Brown et al, 2002;Connors et al, 2001;Humphreys et al, 2004;Owen et al, 2003). TSF and closely related approaches have also been demonstrated to be as effective as, or more effective than, other approaches among several samples of drug users (Carroll et al, 1998b;Crits-Christoph et al, 1999;Wells et al, 1994).…”
mentioning
confidence: 99%
“…There is still little understanding, moreover, of what involvement in AA specifically entails. This involvement has been determined to be a multidimensional construct, one component of which is AA meeting attendance (Allen, 2000;Caldwell and Cutter, 1998;Gilbert, 1991;Morgenstern et al, 1997;Owen et al, 2003;Snow et al, 1994;Tonigan et al, 1995). Other identified components are faith development (Horstmann and Tonigan, 2002), social networks (Kaskutas et al, 2002;Longabaugh et al, 1998) and several AA-related practices, such as declaring a Home Group and engaging in conversations with AA members both before and after meetings (Caldwell and Cutter, 1998).…”
mentioning
confidence: 99%